The Influence of Financial Literacy, Digital Literacy, Mental Accounting, and Financial Inclusion on The Sustainability of Gen Z MSMEs - Riafianola Syahuri; Ifah Rofiqoh (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the influence of financial literacy, digital literacy, mental accounting, and financial inclusion on the sustainability of MSMEs operated by Generation Z in Yogyakarta City. MSMEs managed by young entrepreneurs face challenges related to financial management capabilities, digital technology utilization, and business stability amid rapid economic changes, thereby requiring stronger financial understanding and behavior. The research employs a quantitative approach by distributing questionnaires to 202 MSME actors selected through purposive sampling, and the data were analyzed using SEM-PLS with SmartPLS 4.0. The results indicate that all independent variables have a positive and significant effect on MSME sustainability, with financial inclusion emerging as the most dominant factor. These findings highlight that financial management skills, digital proficiency, structured financial allocation behavior, and access to formal financial services play essential roles in strengthening the resilience and growth of Generation Z businesses amid the rapid pace of digital transformation.